New designs of target and cooling scheme for water cooled divertor in DEMO. (22nd January 2021) - Qian, X.Y.; Peng, X.B.; Song, Y.T.; Mao, X.; Liu, P.; Song, W.; Huang, J.J.; Lu, P.; Wang, L.; Meng, L.Y.
Abstract: Developing a robust and reliable divertor with an adequate heat removal capability is one of the most crucial issues for the realization of DEMO. Although lots of designs and technologies have been accumulated for the water cooled divertor and a full tungsten water cooled divertor for ITER has been successfully developed, there is still a gap to catch up the requirements of DEMO mainly because of the neutron irradiation. For the purpose of putting forward a feasible proposal of the divertor for DEMO concept in a short to medium term, new designs for the target and cooling circuit have been explored in this article. According to the distribution characteristics of heat load and neutron irradiation damage on the divertor and the unique properties of materials, CuCrZr and RAFM are chosen as the heat sink material for the plasma facing unit (PFU) at strike zone and other zone respectively, which is named 'dual PFUs'. A single coolant circuit is applied to both PFUs and a new design ideology of the cooling scheme has been developed. To assess the performance of the designs, corresponding thermal and structural response for the PFUs and thermal-hydraulics analysis for the cooling circuit had been performed. The property of CuCrZr in neutron irradiation environment is the main limitation for the performance of the target. And the new design for cooling circuit can effectively reduce the pressure drop without any negative impact on the divertor by rationally allocating the coolant through outer vertical target to inner vertical target and dome.